Hemodynamic Changes following Anesthesia Induction and LMA Insertion with Propofol, Etomidate, and Propofol + Etomidate - Hamzeh Hosseinzadeh; Samad EJ Golzari; Effat Torabi; Marjan Dehdilani (Journal of Cardiovascular and Thoracic Research, 2013)
Introduction: LMA is a simple supra-laryngeal device which is used to establish and maintain airway. Despite the common use of the LMA, there are no optimal methods for induction of anesthesia that can guarantee a proper insertion. The purpose of this study is comparing three methods of induction of anesthesia (Propofol, Etomidate, Propofol+Etomidate) in the hemodynamic stability after LMA insertion in elective surgeries.Methods: A total of 90 patients with ASA classes I and II undergoing elective surgeries were randomly allocated into one of the following three groups. Before anesthesia induction, all patients were premedicated. Anesthesia induction methods included: Group P (propofol 2.5 mg/kg), Group E (etomidate 0.3 mg/kg) and Group P+E (propofol 1 mg/kg plus etomidate 0.2 mg/kg). Heart rate, systolic blood pressure, diastolic blood pressure, and mean arterial pressure were measured before induction and 30 seconds after induction. Apnea time is recorded in all patients. Number of attempts to laryngeal mask insertion, ease of placement, were compared in three groups.Results: There was no significant difference between demographic data and BIS, SaO2, Etco2 associated diseases, in three group (P>0.5).There is significant difference in hemodynamic (Systolic, diastolic and mean blood pressures) changes between group 1 in comparison with group 2 and group 3. HR was significantly lower in group 1 than group 2 (P=0.16). There was significant difference in the number of attempts and ease of LMA insertion between group 2 in comparison with group 3 and group 1. The duration of apnea in group 2 was a (8.67± 6) min, where as it was (18.10±6.25) min in group 1 and (12.03±6.4) min group 3.Conclusion: Etomidate plus propofol is an effective and alternative to propofol and etomidate for facilitating LMA insertion with the added advantage of lack of cardio-vascular depression